Financial Inclusion and Women Empowerment: A Case Study of Kathmandu Valley - Shah, Pujani (Nepalese Journal of Management, 2025)
This study examines the financial inclusion and women empowerment: a case study of Kathmandu valley. Women empowerment is selected as the dependent variable. Similarly, decision making, self-confidence, entrepreneurial skills, access to resources, leadership skills and self-efficiency are selected as the independent variables. This study is based on primary data with 121 observations. To achieve the purpose of the study, structured questionnaire is prepared. The correlation coefficients and regression models are estimated to test the significance and importance of different factors influencing financial inclusion and women empowerment in Kathmandu valley. The study showed that decision making has a positive impact on women empowerment. It means that better the decision making, higher would be the women empowerment. Similarly, self-confidence has a positive impact on women empowerment. It indicates that increase in self-confidence leads to increase in women empowerment. Moreover, entrepreneurial skills have a positive impact on women empowerment. It means that increase in entrepreneurial skills leads to increase in women empowerment. Likewise, access to resources has a positive impact on women empowerment. It shows that increase in access to resources leads to increase in women empowerment. Similarly, access to resources has positive impact on women empowerment. It shows that higher the access to resources, higher would be the women empowerment. Further, leadership skills have a positive impact on women empowerment. It shows that higher the purchase intention, higher would be the women empowerment. It shows that increase in self-efficiency leads to increase in women empowerment. Similarly, self-efficiency has positive impact on women empowerment